2015
DOI: 10.1039/c4tc01721h
|View full text |Cite
|
Sign up to set email alerts
|

MXene nanoribbons

Abstract: Quasi-one-dimensional nanoribbons have great potential for applications in nanoelectronics and nanospintronics due to their unique quantum confinement effects. In this work, first-principles calculations are carried out to predict the stability as well as magnetic and electronic properties of MXene nanoribbons with either zigzag-or armchair-terminated edges. Three types of MXene recently realized experimentally, i.e. Ti 2 C, Ti 3 C 2 and V 2 C, are considered to construct their corresponding MXene nanoribbons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 30 publications
(43 reference statements)
5
70
0
1
Order By: Relevance
“…Many opportunities and challenges exist simultaneously. These include the preparation of bare MXenes; the exfoliation of new MXenes; the studies on their 1D forms [76,77]; the practical measurements of their magnetic, elastic, and optical properties; and their potential applications. All await further research efforts and increased understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Many opportunities and challenges exist simultaneously. These include the preparation of bare MXenes; the exfoliation of new MXenes; the studies on their 1D forms [76,77]; the practical measurements of their magnetic, elastic, and optical properties; and their potential applications. All await further research efforts and increased understanding.…”
Section: Discussionmentioning
confidence: 99%
“…The first-principles calculations for armchair and zigzag nanoribons of pristine and functionalized Ti 2 C, Ti 3 C 2 , and V 2 C [173] have shown that i) there is a remarkable atomic reconstruction at the edges of nanoribbons, ii) hydrogen functionalization can increase magnetic moment as compared with the pristine nanoribbon, and iii) armchair Ti 2 CO 2 nanoribbon with a width of 7.34 Å exhibits a band gap of ∼1.0 eV, which is significantly larger than that of 2D Ti 2 CO 2 (∼ 0.24 eV) [39]. It is also shown that the hole and electron carrier mobility of the Ti 2 CO 2 nanoribbon can be tuned by the width as well as the edge engineering [174].…”
Section: Nanoribbon Nanotube and Heterostructure Mxenesmentioning
confidence: 99%
“…[103] Due to their excellent mechanical properties, MXenes can be applied to wearable devices. [50,106] The electronic band structure of most M n+1 X n is compact, which results in the metallic conductivity of numerous M n+1 X n flakes. [104] The electronic performance of MXene should be considered once they are seriously proposed for application in the electronic industry.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…[102] Moreover, the Ti 3 C 2 T x /CNT composite shows excellent tensile properties (up to 130% strain). [106] The narrow bandgap of Ti 3 C 2 T x flakes indicates that Ti 3 C 2 T x flakes are semiconductors. [105] It is obvious that the conductivity of MXenes mainly depends on its composition.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
See 1 more Smart Citation